A compact synthetic aperture digital holographic microscope with mechanical movement-free beam scanning and optimized active aberration compensation for isotropic resolution enhancement. (November 2020) - Deng, Yuanbo; Huang, Chung-Hsuan; Vinoth, B.; Chu, Daping; Lai, Xin-Ji; Cheng, Chau-Jern
Highlights: Development of a compact mechanical movement-free beam scanning architecture for synthetic aperture digital holographic microscopy. High-quality point spread function was achieved for a wide range of scanning angles by designing the optimized computer-generated holograms. An accurate aberration compensation is demonstrated with isotropic resolution of 150 nm for the wavelength of 532 nm. Abstract: This study proposes and demonstrates a compact synthetic aperture digital holographic microscope (SA-DHM) with mechanical movement-free beam scanning and optimized active aberration compensation. The SA-DHM system is equipped with a phase-only liquid crystal on silicon (LCoS) device as an active optical element to achieve a compact mechanical movement-free beam steering architecture with aberration correction. A rigorous optimization is conducted to modulate the LCoS device using the designed computer-generated holograms (CGH) to generate a high-quality point spread functions (PSF) for a wide range of scanning angles. An accurate aberration correction is studied with and without oil immersed conditions on microscope objective lens. The performance of the proposed method is analyzed with Siemens star target and the results show its potential capability to achieve isotropic resolution enhancement.